Objective and noninvasive biochemical markers in rheumatoid arthritis: where are we and where are we going?. (4th March 2021) - Bay-Jensen, Anne C.; Siebuhr, Anne Sofie; Damgaard, Dres; Drobinski, Patryk; Thudium, Christian; Mortensen, Joachim; Nielsen, Claus H
ABSTRACT: Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disease that affects approximately 1% of the adult population. RA is multi-factorial, and as such our understanding of the molecular pathways involved in the disease is currently limited. An increasing number of studies have suggested that several molecular phenotypes (i.e. endotypes) of RA exist, and that different endotypes respond differently to various treatments. Biochemical markers may be an attractive means for achieving precision medicine, as they are objective and easily obtainable. Areas covered: We searched recent publications on biochemical markers in RA as either diagnostic or prognostic markers, or as markers of disease activity. Here, we provide a narrative overview of different classes of markers, such as autoantibodies, citrulline products, markers of tissue turnover and cytokines, that have been tested in clinical cohorts or trials including RA patients. Expert opinion: Although many biochemical markers have been identified and tested, few are currently being used in clinical practice. As more treatment options are becoming available, the need for precision medicine tools that can aid physicians and patients in choosing the right treatment is growing.